THE ROLE OF BRAND PREFERENCE IN MEDIATING THE INFLUENCE OF PERCEIVED PRICE ON REPURCHASE INTENTION (Study of Netflix Streaming Service Consumers in Denpasar City) - I Made Denis Agung Prastya; Gede Suparna (Adisam Publisher, 2024)
One act of using the internet with the most time spent is watching services in video form, such as watching films or drama series. Various brands of subscription video service providers are offered on the market, one of which is the Netflix brand which is known as a pioneer. This research aims to determine the effect of perceived price on repurchase intention through brand preference among Netflix streaming service consumers in Denpasar City. This research used a purposive sampling technique with a sample size of 120 respondents. Data was collected using a questionnaire and analyzed using path analysis techniques, Sobel test, and Variance Accounted For (VAF). The research results show that perceived price and brand preference have a positive and significant effect on repurchase intention; perceived price influences brand preference; and brand preference is able to partially mediate the influence of perceived price on repurchase intention. The theoretical implications of this research are to add to empirical studies and confirm the influence of brand preference in mediating the influence of perceived price on repurchase intention. From these results, it is recommended that Netflix improve and maintain competitive pricing strategies and continue to innovate to strengthen brand preferences, thereby increasing repurchase intentions among consumers.